Conflict and Cooperation in International Relations: Theoretical Contributions of the Debate between New Realism and Neoliberalism - Ali, Omran (Humanities Journal of University of Zakho, 2020)
This paper deals with the debate between neo-realism and neo-liberalism within the field of international relations and highlights the most important propositions of the two theories, especially regarding their views on the structure of international relations and whether it is characterized by anarchy and conflict or cooperation. The study of conflict and cooperation in international relations has been one of the main tasks of research and analysis for theorists and researchers of international relations, and this conflict-cooperation nexus has become the main issue in the debate between the two prevailing theories in international relations. Neorealism and neoliberalism are the most influential theories on international relations, and the debate between them has considered one of the most important one in the field of international relations. This research seeks to clarify and explain the theoretical contributions of each of the two theories regarding conflict and cooperation in international relations, and the extent to which neoliberal assumptions, especially with regard to the role of international institutions in increasing international cooperation, has contributed to reducing the dominance of the realistic vision in international relations, especially with regard to conflict and anarchy. It argues that the debate between neorealism and neoliberalism did not significantly contribute to developing the theory of international relations, as this debate did not contribute significantly to reducing the dominance of power politics in international relations and solving the international problems resulting from it.